The Role of Investor Gut Feel in Managing Complexity and Extreme Risk - Huang, Laura (Academy of Management Journal, 2018)
Securing financial resources from investors is a key challenge for many early-stage entrepreneurial ventures. Given the inherent uncertainty surrounding a decision to invest in these ventures, prior research has found that experienced investors rely heavily on their investor gut feel—that is, dynamic expertise-based emotion-cognitions specific to the entrepreneurship context. In this paper, I inductively find that rather than being based on rapid, nonconscious impulse, as much of prior literature would suggest, what investors call their “gut feel” is an elaborate “intuiting process.” This process serves a distinct purpose: it emboldens investors to make investments that would otherwise be considered overly risky and likely to lead to failure. In the theoretical model I present, I delineate how investors are guided by a predisposed stance on risk and uncertainty, which dictates the approach investors take toward managing the complexity of an investment opportunity—and how they cognitively and emotionally reframe investment risk into a compelling narrative that transcends avoidance behavior and leads investors to invest. These findings expand our overall understanding of the complex ways in which investors contend with the risks and uncertainties in entrepreneurial finance.